2011
DOI: 10.1007/s10815-011-9547-3
|View full text |Cite
|
Sign up to set email alerts
|

The human postmenopausal ovary as a tool for evaluation of cryopreservation protocols towards whole ovary cryopreservation

Abstract: Purpose Cryopreservation of a complete ovary may be a future method for fertility preservation in cancer patients. Difficulties exist in cryopreservation of the relatively large ovarian tissue mass. This study evaluates whether a human postmenopausal ovary can be used, as a complement to animal models, in studies of this research field. Methods Postmenopausal human ovaries (n=10) were isolated and flushed through ovarian arteries with either the cryoprotectant dimethylsulphoxide or Ringer-Acetate, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, the relatively intact histomorphology of both the arterial and venous ovarian pedicles in both groups after the extended ovarian perfusion, together with the good cellular survival and minimal tissue damage is a significant achievement considering the long perfusion times explored. Our results are consistent with, and expand on, the previous short-time ovarian perfusion studies: 2 h of perfusion in ewes (Wallin et al 2009), 5 h in human (Abrahamsson et al 1990;Milenkovic et al 2011a), 12 h in rabbit (Lambertsen et al 1976;Hamada et al 1977Hamada et al , 1979Kobayashi et al 1981a) and 20 h in rat and mouse (Koos et al 1984;Sogn et al 1984;Brännström and Flaherty 1995). Our results support the findings of another study that used a complex perfusion medium supplemented with insulin, IGF-I and FSH that resulted in a successful 96-h long perfusion time (Maffei et al 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the relatively intact histomorphology of both the arterial and venous ovarian pedicles in both groups after the extended ovarian perfusion, together with the good cellular survival and minimal tissue damage is a significant achievement considering the long perfusion times explored. Our results are consistent with, and expand on, the previous short-time ovarian perfusion studies: 2 h of perfusion in ewes (Wallin et al 2009), 5 h in human (Abrahamsson et al 1990;Milenkovic et al 2011a), 12 h in rabbit (Lambertsen et al 1976;Hamada et al 1977Hamada et al , 1979Kobayashi et al 1981a) and 20 h in rat and mouse (Koos et al 1984;Sogn et al 1984;Brännström and Flaherty 1995). Our results support the findings of another study that used a complex perfusion medium supplemented with insulin, IGF-I and FSH that resulted in a successful 96-h long perfusion time (Maffei et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated successful harvesting of oocytes and to our knowledge, this is the longest ex vivo perfusion time (7 days) described to date for ewe ovaries. A number of studies have been performed on ovarian tissue perfusion from rodents (Koos et al 1984;Sogn et al 1984;Brännström et al 1987;Brännström and Flaherty 1995), rabbit (Lambertsen et al 1976;Hamada et al 1977Hamada et al , 1979Kobayashi et al 1981a), sheep (Wallin et al 2009;Milenkovic et al 2011b;Maffei et al 2016) and also from human tissue (Stähler et al 1974;Abrahamsson et al 1990;Milenkovic et al 2011a;McLaughlin et al 2018). However, a complete follicular development in vitro with subsequent oocyte maturation and live offspring has only been successful in rodent models (Eppig and Schroeder 1989;O'Brien et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, cryopreservation protocols must be adapted to human ovaries. Given their scant availability, initial studies could be conducted with postmenopausal ovaries, as proposed by Milenkovic et al [ 141 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major issue when working with premenopausal whole human ovaries is their availability. In order to facilitate further research into development of an optimal freezing/thawing protocol, Milenkovic et al proposed using postmenopausal ovaries [ 141 ]. Indeed, this would initially allow us to establish and improve cryopreservation protocols respecting the vasculature and stromal architecture of the human ovary, since postmenopausal ovaries are free of follicles.…”
Section: What Has Been Done In Humans So Far?mentioning
confidence: 99%